Vegetative propagation of Pappea capensis Eckl.&Zeyh. (Jacket plum) by means of stem cuttings and air layers - Du Toit, Elsie Sophia (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2010.